Projekt zintegrowanych zajęć edukacyjnych dla uczniów klasy III szkoły podstawowej pt. "Mieszkańcy uli - pszczoły" = An Integrated Educational Project for Third Grade Primary School Students: The Inhabitants of the hives - Bees - Worobel, Karolina; Wypych, Anna; Nyczaj-Drąg, Mirosława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The project Inhabitants of the hives - Bees aimed at third-grade primary school students, seeks to broaden their knowledge about bees, their role in the ecosystem, and their importance to humans. The key components of the project are based on the concept of knowledge integration in early education, in which students acquire knowledge by combining different disciplines into coherent, interdisciplinary learning units.
Keywords: edukacja wczesnoszkolna; integracja wiedzy; ekosystem; pszczoły; praca grupowa; odpowiedzialność ekologiczna; interdyscyplinarność; kreatywność; aktywne uczenie; early childhood education; knowledge integration; ecosystem; bees; group work; ecological responsibility; interdisciplinarity; creativity; active learning